Temperature dependence ofthe spin-Iattice interaction for Gd3+ in Th02 and ce02 - Oseroff, S. B.; Calvo, R. (Instituto de Física "Dr. José A. Balseiro". Universidad Nacional de Cuyo, 1971)
Fil: Oseroff, S. B. Comisión Nacional de Energía Atómica; Argentina